Undergraduate Adult Applicants Who Did Not Enroll for the Semester of Application 2000-2005 - Cristian Can Stoicescu (Adult Education Research Conference, 2008)
This study shows that from 2000 through 2005 half of undergraduate adult applicants at Penn State never enrolled to the University. This represents a waste of important human and financial resources, which seriously affects the University’s well-being and has implications for those assisting adults through the applicant recruitment processes.
Keywords: undergraduate; adult; applicant; enrollment